2020
DOI: 10.3390/s20123536
|View full text |Cite
|
Sign up to set email alerts
|

A Null Space-Based Blind Source Separation for Fetal Electrocardiogram Signals

Abstract: This paper presents a new non-invasive deterministic algorithm of extracting the fetal Electrocardiogram (FECG) signal based on a new null space idempotent transformation matrix (NSITM). The mixture matrix is used to compute the ITM. Then, the fetal ECG (FECG) and maternal ECG (MECG) signals are extracted from the null space of the ITM. Next, MECG and FECG peaks detection, control logic, and adaptive comb filter are used to remove the unwanted MECG component from the raw FECG signal, thus extracting a clean FE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 45 publications
(87 reference statements)
0
12
0
Order By: Relevance
“…In addition, the method has proven to be cost-effective and therefore suitable for implementation within a battery-powered remote monitoring device. Research of Taha et al 39 introduced a blind source separation-based method, and a new null space idempotent transformation matrix (NSITM) algorithm. When testing the method on signals from the Challenge 2013 dataset, an average value of ACC = 97.00% was achieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the method has proven to be cost-effective and therefore suitable for implementation within a battery-powered remote monitoring device. Research of Taha et al 39 introduced a blind source separation-based method, and a new null space idempotent transformation matrix (NSITM) algorithm. When testing the method on signals from the Challenge 2013 dataset, an average value of ACC = 97.00% was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Research of Taha et al 39 introduced a blind source separation-based method, and a new null space idempotent transformation matrix (NSITM) algorithm. When testing the method on signals from the Challenge 2013 dataset, an average value of ACC = 97.00% was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Blind source separation (BSS), sometimes referred to as blind signal processing, is capable of recovering a source signal from an observed signal in the absence of critical information, such as source and channel [ 1 , 2 , 3 ]. Due to its high adaptability and other advantages, BSS has been employed in a variety of research fields in recent years, such as image processing, medical evaluation, radar analysis, speech recognition, and machinery [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, abdominal mixed signals of pregnant women are complex, comprising MECG signals, FECG signals, baseline drift, power frequency interference, and noises [ 4 ]. Blind source separation (BSS) [ 5 ] can be used to extract FECG signals from the abdominal mixed signals, but there is a large amount of residual noises in the extracted FECG signals.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results showed that TS combined with the FastICA algorithm yielded the best performance, with a high signal-to-noise ratio (SNR). The FastICA algorithm uses approximate negative entropy and Newton iterative methods to reduce the amount of computation, which has the advantage of fast convergence and is a widely used signal separation method [ 5 ]. However, its convergence performance is greatly affected by the initial weight [ 13 ].…”
Section: Introductionmentioning
confidence: 99%